Lithium ion battery
By using silicon-carbon negative electrode materials in lithium-ion batteries and optimizing the composition of SEI film-forming additives, the problem of expansion and deterioration of silicon negative electrodes in traditional lithium-ion batteries is solved, and the safety, rate performance and cycling performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411602030.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The composition of traditional lithium-ion batteries and silicon negative electrodes can easily lead to severe expansion and deterioration, significantly reduced circulation performance and reduced safety performance.
By using silicon-carbon negative electrode material in lithium-ion batteries, and controlling its spherical shape and the mass content ratio of difluorovinyl carbonate to fluorovinyl carbonate in the electrolyte, the composition of SEI film film forming additives is optimized to generate silicon SEI polymer film with higher matching degree of carbon anode material.
It significantly improves the safety and reliability of silicon negative electrode lithium-ion batteries, and improves the rate performance and long cycle performance of lithium-ion batteries.
Smart Images

Figure CN119481279A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery. Background Art
[0002] With the rapid development of portable electronic devices and electric vehicles, there is an increasing demand for rechargeable batteries with high energy density, high safety and long cycle life. Lithium-ion batteries (LIBs) have become the preferred energy storage solution due to their high energy density, low self-discharge rate and excellent cycle performance. As a key component of lithium-ion batteries, electrolyte plays a vital role in the electrochemical performance and safety of batteries.
[0003] As the demand for energy density of lithium-ion batteries increases, silicon-based negative electrodes have attracted much attention from researchers due to their high energy density improvement brought by their high gram capacity. Traditional lithium-ion battery compositions with silicon negative electrodes are prone to severe expansion and degradation, significantly reduced cycle performance, and decreased safety performance. Therefore, it is necessary to develop a lithium-ion battery system that matches the characteristics of the silicon negative electrode to improve the performance of the silicon negative electrode system. Summary of the invention
[0004] Based on the above problems, the present invention provides a lithium-ion battery that can maintain high electrochemical performance while having better compatibility with silicon-carbon negative electrodes, significantly improving the safety and reliability of silicon negative electrode lithium-ion batteries, and enhancing the rate performance and cycle performance of lithium-ion batteries.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A first aspect of the present invention provides a lithium ion battery, comprising a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon negative electrode material;
[0007] The sphericity of the silicon-carbon negative electrode material is X1, and 0.5≤X1≤1;
[0008] The electrolyte includes an additive, wherein the mass content ratio of difluoroethylene carbonate to fluoroethylene carbonate in the additive is X2, and 0.1≤X2≤1;
[0009] Among them, 0.5≤X1 / X2≤5.
[0010] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0011] When the sphericity of the silicon-carbon negative electrode material particles of the present invention and the mass content ratio of DFEC / FEC satisfy a certain relationship, the composition of the SEI film-forming additive can be optimized to be more compatible with the spherical silicon-carbon negative electrode material particles, thereby generating an SEI polymer film with a higher matching degree with the silicon-carbon negative electrode material, significantly improving the cycle performance of the silicon-carbon negative electrode material, and being able to have better compatibility with the silicon-carbon negative electrode while maintaining high electrochemical performance, significantly improving the safety and reliability of silicon negative electrode lithium-ion batteries, and thereby improving the rate performance and long cycle performance of silicon-carbon negative electrode lithium-ion batteries.
[0012] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 A schematic top view of the tab structure of the positive and negative electrodes of a lithium-ion battery provided in one embodiment of the present invention. DETAILED DESCRIPTION
[0014] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0015] A first aspect of the present invention provides a lithium ion battery, comprising a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon negative electrode material;
[0016] The sphericity of the silicon-carbon negative electrode material is X1, and 0.5≤X1≤1;
[0017] The electrolyte includes an additive, wherein the mass content ratio of difluoroethylene carbonate to fluoroethylene carbonate in the additive is X2, and 0.1≤X2≤1;
[0018] Among them, 0.5≤X1 / X2≤5.
[0019] In the present invention, the sphericity of the silicon-carbon negative electrode material is X1, and 0.5≤X1≤1, wherein the sphericity of the silicon-carbon negative electrode material represents the spherical state of the silicon-carbon negative electrode material particles, and the higher the sphericity of the silicon-carbon negative electrode material particles, the closer the spherical state is to the exemplary spherical state of the spherical shape, and the testing method is: by using image processing software (such as Image Pro Plus) to analyze the image of each particle in the SEM photo of the silicon-carbon composite material under a certain magnification (such as 2500 times), the perimeter and area of each particle are obtained, and the perimeter equivalent radius r1 and area equivalent radius r2 of each particle are calculated respectively, then the sphericity of each particle S=r2 / r1, and then the sphericity of each particle is quantitatively weighted averaged to obtain the average sphericity of the silicon-carbon composite material. The value of the sphericity X1 of the silicon-carbon negative electrode material can be 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, 0.96, 0.97, 0.98, 0.99, 1.
[0020] In the present invention, the mass content ratio of bisfluoroethylene carbonate to fluoroethylene carbonate in the additive is X2, and 0.1≤X2≤1, wherein, illustratively, the value of the ratio X2 of bisfluoroethylene carbonate to fluoroethylene carbonate in the additive can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1. In a preferred embodiment, 0.2≤X2≤0.6.
[0021] When a silicon-carbon negative electrode material with a certain spherical state is made into a silicon-carbon negative electrode battery, the negative electrode sheet will expand in a spherical form in an irregular manner during the charge and discharge process, thereby improving the uniformity of the amorphous expansion, avoiding the impact and collision of the sharp parts of the irregular silicon-carbon particles on other particles during the expansion process, and reducing the physical damage to the SEI film. Therefore, the amount of film-forming additives (such as fluoroethylene carbonate FEC) can be appropriately reduced, thereby avoiding continuous thickening of SEI, alleviating the high impedance caused by continuous film formation, and ensuring that the lithium-ion battery has better rate performance.
[0022] However, the higher the sphericity of the silicon-carbon negative electrode material particles, the more stable SEI components are needed to replace the continuously repairing SEI components. The SEI polymer film generated after the film formation of difluoroethylene carbonate (DFEC) has a high degree of polymerization and is rich in LiF. At the same time, the interlayer hydrogen bonds of its polymer film are stronger. Therefore, it is more beneficial to silicon-carbon negative electrode materials with high sphericity. However, DFEC is only stable in the initial film formation, and its continuous repair ability during the cycle is weak. Fluorinated ethylene carbonate (FEC) has very good SEI repair ability during the cycle. Therefore, the two film-forming additives are used in combination, and the ratio of the two is controlled at the same time, which can ensure that the stability of the initial interface film and the stability of the interface film during long cycles are both good.
[0023] In summary, the present invention can enhance the safety and reliability of silicon negative electrode lithium ion batteries and improve the rate performance and long cycle performance of silicon carbon negative electrode lithium ion batteries by controlling the sphericity of silicon carbon negative electrode material particles and the mass content ratio of DFEC / FEC.
[0024] Further, in the present invention, the sphericity X1 of the silicon-carbon negative electrode material particles and the mass content ratio X2 of DFEC / FEC satisfy 0.5≤X1 / X2≤5. Exemplarily, the values of X1 / X2 can be 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5. When X1 / X2 is less than 0.5, the sphericity of the silicon-carbon negative electrode material particles is small, and the uniformity of amorphous expansion decreases, which is not conducive to the repair of the SEI film during the long cycle process and affects the long cycle performance of the lithium-ion battery; when X1 / X2 is greater than 5, the mass content ratio of DFEC / FEC is too small, and the content of DFEC is small, which will affect the stability of the initial interface film of SEI, and because the volume change of the silicon-carbon negative electrode material in the initial stage of expansion and degradation is more obvious, it will cause irreversible physical damage to the SEI film, which is easy to cause continuous thickening of SEI, which is not conducive to the rate performance of the lithium-ion battery. In a preferred embodiment, 0.5≤X1 / X2≤3.
[0025] In a specific embodiment, based on the total mass of the electrolyte, the mass content of the bisfluoroethylene carbonate (DFEC) is 0.1wt% to 10wt%. Exemplarily, the mass content of the bisfluoroethylene carbonate can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%. The initial interface stability of the SEI film generated by bisfluoroethylene carbonate is relatively excellent, so its mass content should not be too small, but due to its weak continuous repair ability during long cycles, its mass content should not exceed 10wt% of the total mass of the electrolyte. In a preferred embodiment, based on the total mass of the electrolyte, the mass content of the bisfluoroethylene carbonate is 1wt% to 10wt%.
[0026] In a specific embodiment, based on the total mass of the electrolyte, the mass content of the fluoroethylene carbonate is 0.5wt% to 20wt%. For example, the mass content of the fluoroethylene carbonate can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.5wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%. Fluoroethylene carbonate (FEC) has very good SEI repair ability in the long cycle process, so its mass content should not be too little, but it should not be too much, because too much FEC content will cause the SEI film to continue to thicken in the long cycle process, so that the impedance of the negative electrode sheet increases, affecting the rate performance of the lithium ion battery. In a preferred embodiment, the mass content of the fluoroethylene carbonate is 2 wt% to 20 wt%.
[0027] In a specific embodiment, the electrolyte includes bis(trifluoromethylsulfonyl)imide magnesium, and based on the total mass of the electrolyte, the mass content of the bis(trifluoromethylsulfonyl)imide magnesium is Y1 wt%, and 0.1wt%≤Y1 wt%≤8wt%; exemplary, the mass content Y1wt% of the bis(trifluoromethylsulfonyl)imide magnesium can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%. In a preferred embodiment, 0.5wt%≤Y1wt%≤5wt%.
[0028] In a specific embodiment, the silicon content of the negative electrode is Y2%, and 3%≤Y2%≤60%; exemplarily, the silicon content Y2% of the negative electrode can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, or 60%. It should be noted that the silicon content Y2% of the negative electrode refers to the mass percentage of silicon in the negative electrode active material layer or the negative electrode active material, and the negative electrode active material is coated on one side or both sides of the negative electrode current collector to form the negative electrode active material layer; in addition, the test method for the silicon content of the negative electrode is the ash test method, which divides the ash value of the negative electrode active layer (i.e., the inorganic content remaining in the negative electrode active layer after high-temperature calcination) by the molar mass of silicon dioxide (60) and then multiplies it by the molar mass of silicon (28), that is, the percentage of silicon in the negative electrode active material layer, that is, the silicon content Y2% of the negative electrode. In a preferred embodiment, 10%≤Y2%≤40%.
[0029] Magnesium bis(trifluoromethylsulfonyl)imide (mgTFSi) can generate a stable magnesium-silicon alloy layer on the surface of the silicon-carbon negative electrode, reducing the formation of the initial lithium-silicon alloy. Since the stability of the lithium-silicon alloy is not as good as that of the magnesium-silicon alloy, the generated magnesium-silicon alloy layer can improve the stability of the silicon-carbon negative electrode material and reduce the side reactions of the electrolyte on the surface of the silicon-carbon negative electrode material. At the same time, the generated magnesium-silicon alloy layer can increase the migration rate of lithium ions on the surface of the silicon negative electrode particles and improve the rate performance of lithium-ion batteries.
[0030] Furthermore, in a specific embodiment, 0.01≤Y1 / Y2≤0.2. Exemplarily, the value of Y1 / Y2 can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2. In a preferred embodiment, 0.05≤Y1 / Y2≤0.1. Furthermore, the present invention can ensure the generation of a more stable magnesium-silicon alloy layer by controlling the ratio of mgTFSi to the silicon content in the negative electrode. If the ratio is too low, the amount of mgTFSi is insufficient, the silicon content of the negative electrode is too much, and the generation of the silicon surface interface layer cannot be ensured; if the ratio is too high, the amount of mgTFSi is too much, and the silicon content of the negative electrode is too little, it will lead to the accumulation of metal ions in the interface layer, deteriorating the self-discharge while significantly improving the interface lithium ion transmission rate. Moreover, when the film-forming additive DFEC in the electrolyte is combined with FEC, it is easy to generate more LiF and Li2CO3, which will cause the storage gas production of lithium-ion batteries to deteriorate. The stable magnesium-silicon alloy layer generated by controlling the ratio of mgTFSi to the silicon content of the negative electrode can effectively improve the interface stability of the negative electrode, thereby reducing the risk of high-temperature storage gas production performance degradation and effectively improving the defects caused by adjusting the film-forming additives.
[0031] In a specific embodiment, the electrolyte includes propyl acetate. Based on the total mass of the electrolyte, the mass content of propyl acetate is Z1, and 2wt%≤Z1 wt%≤60wt%; illustratively, the mass content Z1 of propyl acetate can be 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%. Propyl acetate (PA) has low viscosity and high conductivity, which can significantly improve the lithium ion transfer rate and the rate performance of the silicon-carbon negative electrode system. At the same time, it has low density and can quickly infiltrate the silicon-carbon negative electrode material particles, forming a rapid coating effect on the silicon-carbon negative electrode material particles, and improving the uniform lithium insertion of lithium ions around the silicon-carbon negative electrode material particles, avoiding irregular expansion caused by local short circuits, but PA has deterioration on the high temperature performance of lithium batteries, so it is necessary to control the appropriate amount and match the high temperature performance application of the system. In a preferred embodiment, 10wt%≤Z1wt%≤30wt%.
[0032] In a specific embodiment, the specific surface area of the silicon-carbon negative electrode material is Z2 m 2 / g, and 0.5m 2 / g≤Z2m 2 / g≤10m 2 / g; Exemplarily, the particle specific surface area of the silicon-carbon negative electrode material is Z2 m 2 / g can be 0.5m 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g, 5.5m 2 / g, 6m 2 / g, 6.5m 2 / g, 7m 2 / g, 7.5m 2 / g, 8m 2 / g, 8.5m 2 / g, 9m 2 / g, 9.5m 2 / g, 10m 2 / g. In a preferred embodiment, 2m 2 / g≤Z2m2 / g≤5m 2 / g.
[0033] Further, in a specific embodiment, 10≤Z1*Z2≤300. Exemplarily, the value of Z1*Z2 can be 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300. The larger the specific surface area of the particles of the silicon-carbon negative electrode material, the smaller the particles, and the better the kinetics, so the amount of PA can be reduced, and when the specific surface area is smaller, the larger the particles, the worse the kinetic performance, so more PA is needed to improve the kinetic performance, and the larger the particles, the better the high temperature performance of the system, so by controlling the amount of PA and the specific surface area of the particles of the silicon-carbon negative electrode material, it can be ensured that the kinetic performance is better and the high temperature performance is also better. In a preferred embodiment, 30≤Z1*Z2≤100.
[0034] In a specific embodiment, the lithium-ion battery further comprises a positive electrode, and the vertical distance between the positive electrode ear of the positive electrode and the same side edge of the negative electrode ear of the negative electrode is L, such as Figure 1 As shown, it is a schematic top view of the structure of the positive and negative pole ears of a lithium-ion battery provided by an embodiment of the present invention, and the vertical distance L satisfies 10mm≤L≤35mm. Exemplarily, the vertical distance L between the same side edges of the positive pole ear and the negative pole ear can be 10mm, 12mm, 14mm, 16mm, 18mm, 20mm, 22mm, 24mm, 26mm, 28mm, 30mm, 32mm, 33mm, 35mm.
[0035] Due to the poor conductivity of the silicon-carbon negative electrode, the polarization during the charge and discharge process increases. Therefore, the battery will generate more heat and it will be more difficult to dissipate heat during the charge and discharge process. The spacing between the positive and negative pole ears will affect the heat generation and heat dissipation rate of the lithium battery. When the vertical distance L between the same side edges of the positive and negative pole ears is less than 10mm, the distance between the ears is too small. The ears are the heat diffusion center during the charge and discharge process. Since the distance between the ears is too small, the thermal effect is easily superimposed, resulting in excessive temperature in the negative electrode area of the ears, which is prone to thermal runaway. When the vertical distance L between the same side edges of the positive and negative pole ears is too large, there is no thermal effect superposition between the ears, resulting in the dynamic performance near the ears not being improved by the temperature, resulting in lithium precipitation very easily near the ears, deteriorating the dynamic performance. Therefore, by adjusting the distance between the ears of the positive and negative electrodes of the silicon-carbon system battery, it is possible to ensure that the heat generation and heat dissipation of the silicon-carbon negative electrode are in the optimal state, thereby avoiding degradation of the lithium battery performance due to thermal effects.
[0036] In a specific embodiment, the electrolyte further includes a lithium salt, and the lithium salt includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorooxalate borate, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorobis(oxalato)phosphate, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium tris(trifluoromethylsulfonyl)methyl, and lithium bis(trifluoromethylsulfonyl)imide.
[0037] In a specific embodiment, the electrolyte further includes an organic solvent, and the organic solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, n-butyl acetate, isobutyl acetate, n-pentyl acetate, isopentyl acetate, ethyl propionate, n-propyl propionate, methyl butyrate, ethyl butyrate, and n-ethyl butyrate.
[0038] In a specific embodiment, the positive electrode includes a layered lithium composite oxide with the chemical formula Li (1+x) Ni y Co z M (1-y-z) O2, where -0.1 ≤ x ≤ 1; 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, and 0 ≤ y + z ≤ 1; where M is one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.
[0039] In a specific embodiment, the negative electrode active material further includes a carbon-based negative electrode material, where the carbon-based negative electrode material includes at least one of artificial graphite, natural graphite, mesocarbon microbeads, hard carbon, and soft carbon.
[0040] In a specific embodiment, the silicon-carbon negative electrode material includes at least one of nano-silicon (Si), silicon oxide (SiO x (0 < x < 2)), and silicon-carbon.
[0041] In the present invention, the preparation method of the lithium-ion battery is as follows: Stack the prepared positive electrode sheet, separator, and negative electrode sheet in sequence, ensure that the separator is between the positive and negative electrode sheets to play an isolation role, and then obtain an un-injected bare battery cell by winding; Place the bare battery cell in an outer packaging foil, inject the prepared electrolyte into the dried bare battery cell, and obtain the required lithium-ion battery through processes such as vacuum packaging, standing, formation, shaping, and sorting.
[0042] The following will further elaborate on the present invention in detail with specific embodiments. It should be understood that the following embodiments are only for exemplarily illustrating and explaining the present invention, and should not be construed as limiting the protection scope of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope intended to be protected by the present invention.
[0043] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0044] Example 1
[0045] The lithium ion battery of the present invention is obtained by the following method, see Table 1 for details:
[0046] (1) Preparation of positive electrode
[0047] Layered lithium composite oxide LiCoO4, polyvinylidene fluoride (PVDF), conductive carbon black SP (super P) and carbon nanotubes (CNT) are mixed in a mass ratio of 97.2:1:1.3:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of an aluminum foil; the coated aluminum foil is dried, and then rolled and cut to obtain the desired positive electrode sheet.
[0048] (2) Negative electrode preparation
[0049] Artificial graphite, silicon carbon (whose sphericity X1 is 0.7, specific surface area Z2 is 4m 2 / g), sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) were mixed in a mass ratio of 79.5:15:2.5:1.5:1:0.5 and added with deionized water, and a negative electrode active material was obtained under the action of a vacuum mixer, wherein the silicon content Y2% in the negative electrode active material was 35%; the negative electrode active material was uniformly coated on both surfaces of the copper foil; the coated copper foil was dried at room temperature, then transferred to an oven at 80°C for drying for 10 hours, and then cold pressed and cut to obtain a negative electrode sheet. In addition, a tab was provided on one side of the positive electrode sheet and the negative electrode sheet, and the spacing L between the positive tab and the negative tab was 25 mm.
[0050] (3) Preparation of electrolyte
[0051] In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), EC / PC / PP / PA were mixed in a mass ratio of 10 / 15 / 55 / 20, and then lithium hexafluorophosphate (LiPF6) with a total mass content of 14.38wt% based on the total mass content of the electrolyte was quickly added as a lithium salt, and after dissolution, 4wt% of difluoroethylene carbonate (DFEC) and 16wt% of fluoroethylene carbonate (FEC) (X2 = 0.25) based on the total mass content of the electrolyte were added, as well as other additives, specifically: 3wt% (Y1 wt%) of magnesium bis(trifluoromethylsulfonyl)imide (mgTFSi), 2wt% of 1,3-propane sultone (PS), 2wt% of 1,3,6-hexanetrinitrile (HTCN), 2wt% of adiponitrile (ADN), 1wt% of succinonitrile (SN), and stirred evenly. After passing the moisture and free acid tests, the desired electrolyte was obtained.
[0052] (4) Preparation of batteries
[0053] The positive electrode sheet of step 1), the negative electrode sheet of step 2) and the separator (wherein the adhesion between the separator and the negative electrode sheet prepared above is measured to be 14N / m) are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, and the electrolyte of step 3) is injected into the outer packaging, and a lithium ion battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes. The battery of the present invention has a charge and discharge range of 3.0-4.5V.
[0054] Example 2 Group
[0055] Example 2 was carried out with reference to Example 1, with the only difference being that the spherical state of the silicon-carbon particles was adjusted so that the sphericity X1 of the silicon-carbon particles of the silicon-carbon negative electrode material was changed, as shown in Table 1 for details.
[0056] Example 3 Group
[0057] Example 3 was carried out with reference to Example 1, except that, during the preparation of the electrolyte, the mass contents of difluoroethylene carbonate and fluoroethylene carbonate added to the electrolyte were changed, as shown in Table 1 for details.
[0058] Example 4 Group
[0059] Example 4 was carried out in accordance with Example 1, with the only difference being that the mass ratio of artificial graphite, silicon carbon, sodium carboxymethyl cellulose, styrene-butadiene rubber, conductive carbon black and single-walled carbon nanotubes was changed, so that the silicon content of the negative electrode was changed, as shown in Table 1 for details.
[0060] Example 5 Group
[0061] Example 5 was carried out with reference to Example 1, except that, during the preparation of the electrolyte, the mass content of magnesium bis(trifluoromethylsulfonyl)imide added to the electrolyte was changed, as shown in Table 1 for details.
[0062] Example 6 Group
[0063] Example 6 was carried out in accordance with Example 1, with the only difference being that, during the preparation of the electrolyte, the mass content of propyl acetate added to the electrolyte was changed, as shown in Table 1 for details.
[0064] Example 7 Group
[0065] The seventh embodiment is carried out with reference to the first embodiment, except that the arrangement positions of the positive electrode ear and the negative electrode ear are changed, so that the distance L between the positive electrode ear and the negative electrode ear is changed. Specifically:
[0066] In Example 7-1, the distance L between the positive electrode tab and the negative electrode tab is changed to 10 mm;
[0067] In Example 7-2, the distance L between the positive electrode tab and the negative electrode tab is changed to 35 mm.
[0068] Comparative Example 1 to Comparative Example 4
[0069] Comparative Examples 1 to 4 were carried out with reference to Example 1, with the only difference being that, during the preparation of the electrolyte, the mass contents of difluoroethylene carbonate and fluoroethylene carbonate added to the electrolyte were changed, as shown in Table 1 for details.
[0070] Comparative Example 5 to Comparative Example 6
[0071] Comparative Examples 5 to 6 are carried out with reference to Example 1, with the only difference being that the spherical state of the silicon-carbon particles is adjusted so that the sphericity X1 of the silicon-carbon particles of the silicon-carbon negative electrode material is changed, see Table 1 for details.
[0072] Table 1
[0073]
[0074]
[0075] Lithium-ion battery test example
[0076] The lithium ion batteries obtained in the above examples and comparative examples were tested by the following method, and the test results are recorded in Table 2:
[0077] The test methods for performance parameters are as follows:
[0078] (1) Cycle test of lithium-ion batteries at 25°C
[0079] The lithium-ion battery was placed at 25°C, charged at 1C constant current to the upper voltage limit (4.5V), then charged at 4.5V constant voltage to 0.05C, and left to stand for 5 minutes; then discharged at 0.5C constant current to 3V, and left to stand for 5 minutes. This is a charge and discharge cycle. The capacity retention rate / % of the lithium-ion battery after 1000T of charge / discharge was recorded, and the results are recorded in Table 2.
[0080] (2) High temperature cycle test of lithium-ion batteries at 45°C
[0081] The lithium-ion battery was placed at 45°C, charged at a constant current of 1C to the upper voltage limit (4.5V), then charged at a constant voltage of 4.5V to 0.05C, and left to stand for 5 minutes; then discharged at a constant current of 0.5C to 3V, and left to stand for 5 minutes. This is a charge and discharge cycle. The capacity retention rate / % of the lithium-ion battery after 400T of charge / discharge was recorded, and the results are recorded in Table 2.
[0082] (3) Rate charging test of lithium-ion batteries
[0083] The corresponding battery was placed in a constant temperature environment of 25℃, ① left to stand for 10min, ② first discharged to 3.0V with 0.2C, ③ left to stand for 10min, ④ charged to 4.45V with 3C rate, cut-off current 0.02C, ⑤ left to stand for 10min, ⑥ discharged to 3.0V with 0.2C, ⑦ left to stand for 10min. Steps ④ to ⑦ were cycled 3 times, and the average of the 3 constant current charging ratios was taken. Constant current charging ratio = constant current charging capacity ÷ charging capacity × 100%, see Table 2.
[0084] Table 2
[0085]
[0086]
[0087] From the analysis of Example 1 and Comparative Examples 1 to 6 in Table 1 and Table 2, it can be seen that by controlling the sphericity of the silicon-carbon negative electrode material particles and the mass content ratio of DFEC / FEC, the composition of the SEI film-forming additive that is more compatible with the spherical silicon-carbon negative electrode material particles can be better regulated, thereby generating a SEI polymer film that is more compatible with the silicon-carbon negative electrode material, thereby improving the rate performance and long cycle performance of the silicon-carbon negative electrode lithium-ion battery.
[0088] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
[0089] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A lithium ion battery comprising a negative electrode and an electrolyte, characterized in that: The negative electrode includes a negative electrode active material, and the negative electrode active material includes a silicon-carbon negative electrode material; The sphericity of the silicon-carbon negative electrode material is X1, and 0.5≤X1≤1; The electrolyte includes an additive, wherein the mass content ratio of difluoroethylene carbonate to fluoroethylene carbonate in the additive is X2, and 0.1≤X2≤1; Among them, 0.5≤X1 / X2≤5.
2. The lithium-ion battery according to claim 1, characterized in that 0.2≤X2≤0.6; and / or, 0.5≤X1 / X2≤3.
3. The lithium ion battery according to claim 1 or 2, characterized in that: Based on the total mass of the electrolyte, the mass content of the bisfluoroethylene carbonate is 0.1wt% to 10wt%, more preferably 1wt% to 10wt%.
4. The lithium-ion battery according to claim 3, characterized in that: Based on the total mass of the electrolyte, the mass content of the fluoroethylene carbonate is 0.5wt% to 20wt%, more preferably 2wt% to 20wt%.
5. The lithium-ion battery according to claim 1, characterized in that: The electrolyte includes magnesium bis(trifluoromethylsulfonyl)imide, and the mass content of magnesium bis(trifluoromethylsulfonyl)imide is Y1 wt% based on the total mass of the electrolyte, and 0.1 wt%≤Y1 wt%≤8 wt%; The silicon content of the negative electrode is Y2%, and 3%≤Y2%≤60%; Preferably, 0.01≤Y1 / Y2≤0.
2.
6. The lithium-ion battery according to claim 5, characterized in that: 2wt%≤Y1wt%≤5wt%; and / or, 15%≤Y2%≤40%; and / or, 0.05≤Y1 / Y2≤0.
1.
7. The lithium-ion battery according to claim 1, characterized in that: The electrolyte includes propyl acetate, and based on the total mass of the electrolyte, the mass content of the propyl acetate is Z1, and 2wt%≤Z1wt%≤60wt%; The specific surface area of the silicon-carbon negative electrode material is Z2 m 2 / g, and 0.5m 2 / g≤Z2≤10m 2 / g; Preferably, 10≤Z1*Z2≤300.
8. The lithium-ion battery according to claim 7, characterized in that: 10wt%≤Z1wt%≤30wt%;and / or, 2m 2 / g≤Z2≤5m 2 / g; and / or, 30≤Z1*Z2≤100.
9. The lithium-ion battery according to claim 1, characterized in that: The lithium-ion battery further includes a positive electrode, and a vertical distance between a positive electrode ear of the positive electrode and a same side edge of a negative electrode ear of the negative electrode is L, and 10 mm≤L≤35 mm.
10. The lithium ion battery according to claim 1, characterized in that: The electrolyte also includes a lithium salt, and the lithium salt includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonylimide), lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyllithium, and lithium bis(trifluoromethylsulfonyl)imide; And / or, the electrolyte also includes an organic solvent, and the organic solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, ethyl propionate, n-propyl propionate, methyl butyrate, ethyl butyrate, and ethyl butyrate.
Citation Information
Patent Citations
Lithium-ion battery and manufacturing method thereof
CN102683662A
Non-aqueous electrolyte and battery comprising same
CN114094187A
Electrochemical device and electronic device
CN116169357A
Non-aqueous electrolyte for sodium ion battery and sodium ion battery
CN116598585A
Lithium ion battery
CN117594876A